2021
DOI: 10.1007/s40200-021-00770-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the anti-hyperglycemic and antioxidant effects of wheat bread supplemented with onion peel extract and onion powder in diabetic rats

Abstract: Aim Onion is one of the commonly cultivated and consumed vegetables rich in nutrients and phytochemicals. Various nutraceuticals are found in the outer fleshy layers and dry peel of onion which usually is treated as a common biowaste. Diabetes mellitus is a leading non communicable disease causing hyperglycemia and increased production of free radicals that potentially disrupts antioxidant enzymatic activity. Considering global consumption of wheat, the present study was designed to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 88 publications
0
14
0
1
Order By: Relevance
“…Bread products are also preferred by the elderly, who are at a greater risk of osteoporosis, from different regions in the world [ 18 ]. A study reported that wheat bread supplemented with the antioxidant from onion brought a significant improvement in antioxidant enzyme activities of diabetic rats [ 35 ]. Pastoriza et al [ 36 ] reported the positive effect on the antioxidant defense in the liver of rats after a long-term Maillard reaction products-containing bread crust diet, manifested in increased antioxidant enzyme activities and glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…Bread products are also preferred by the elderly, who are at a greater risk of osteoporosis, from different regions in the world [ 18 ]. A study reported that wheat bread supplemented with the antioxidant from onion brought a significant improvement in antioxidant enzyme activities of diabetic rats [ 35 ]. Pastoriza et al [ 36 ] reported the positive effect on the antioxidant defense in the liver of rats after a long-term Maillard reaction products-containing bread crust diet, manifested in increased antioxidant enzyme activities and glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…These results support the hypothesis that hyperglycemia in diabetes is linked with oxidative stress, the formation of ROS, or the shortage of antioxidant defensive systems [ 23 ]. Furthermore, the considerable reduction in enzymatic and nonenzymatic antioxidants in diabetic rats could be related to an increase in ROS production, as well as the presence of H 2 O 2 and other hydrogen radicals [ 4 , 21 , 24 , 25 ]. Because glutathione is an important nonenzymatic antioxidant involved in maintaining cellular integrity, its depletion signals the advancement of cellular damage caused by free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Kiwifruit is also a good source of antioxidants and natural pancreatic lipase and α -glucosidase inhibitors [ 47 ]. Similarly, diabetic rats given onion as part of their diet had considerably higher body weights and antioxidant enzyme activity [ 25 ]. In diabetic rats, hesperetin, a citrus flavonoid, also attenuates high blood glucose and lipid levels through boosting antioxidant proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches conducted on plants and herbs which contain phenolics in abundant quantities have reported a link between antioxidant activity of extract and inhibition of α-glucosidase activity (Kwon et al, 2006) and particularly Allium cepa bulb have been evaluated for it's several physiological effects including anti-diabetic properties (Wu and Xu, 2011). But for onion outer skin and peels very few studies have investigated their anti-diabetic potential even though they present great concentrations of phytochemicals (Masood et al, 2021). It was stated that methyl alcohol extracts of Allium cepa.…”
Section: α-Amylase/α-glucosidase Inhibition Of Onion Extractsmentioning
confidence: 99%